Risk-takers : alcohol, drugs, sex, and youth - Plant, Martin A. (Tavistock/Routledge, 1992)
Annotation Gives a comprehensive view of youthful involvement with drinking, smoking, illicit drug use and sexual activity, providing a challenging assessment of health education for young people.
Keywords: Teenagers -- Great Britain.; Risk-taking (Psychology) in adolescence -- Great Britain.; Teenagers -- Sexual behavior -- Great Britain.; Teenagers -- Alcohol use -- Great Britain.; Teenagers -- Drug use -- Great Britain.; Drinking of alcoholic beverages.; Risk-taking (Psychology); Drug addiction.; Drug abuse.; Adolescent Behavior; Alcohol Drinking; Adolescent; Risk-Taking; Sexual Behavior; Substance-Related Disorders -- epidemiology; Substance-Related Disorders; United Kingdom; Adolescents -- Grande-Bretagne.; Prise de risque chez l'adolescent -- Grande-Bretagne.; Adolescents -- Sexualité -- Grande-Bretagne.; Adolescents -- Consommation d'alcool -- Grande-Bretagne.; Consommation d'alcool.; Prise de risque.; Toxicomanie.; drug abuse.; drug addiction.; FAMILY & RELATIONSHIPS -- Life Stages -- Adolescence.; FAMILY & RELATIONSHIPS -- Life Stages -- Teenagers.; Drug addiction; Drug abuse; Drinking of alcoholic beverages; Risk-taking (Psychology) in adolescence; Teenagers; Teenagers -- Alcohol use; Teenagers -- Drug use; Teenagers -- Sexual behavior; Great Britain; Jugend; Sexualverhalten; Risikoverhalten; Drogenkonsum; Großbritannien; Adolescents.; Great Britain.